Three faces of context and their implications for career: a study of public sector careers cut short - Cohen, Laurie; Duberley, Joanne (Elsevier, 2015)
This paper examines the impact of context on careers. It is based on a study of senior managers in an English Local Authority. It offers two important contributions: first, an empirical contribution examining how context matters to individuals in their career-making in the setting of the UK public sector. Our findings point to three aspects or faces of context: proximal events, ideology and enduring structural features. The first, context as ideology, attends to meaning-making that is collective in nature, and that incorporates concepts of power, domination, subordination and resistance. Our second refers to the enduring structural features. These are on-going trends and developments, predictable and traceable over the medium to long-term which offer rules and resources, thus structuring opportunity and constraint. Finally, the third face, context as proximal events, refers to (often unexpected) contingencies that arise at particular moments. Although bounded both spatially and temporally, they can significantly impact on career decision making. The second contribution of the paper builds upon this empirical base to develop theoretical and conceptual understanding of the link between career and context, illustrating the interconnectedness of the various faces of context and the dynamic ways in which these influence career-making over time.